A pair-oriented requirements engineering approach for analysing multi-lingual requirements - Kamalrudin, Massila; Sidek, Safiah; Salleh, Norsaremah; Hosking, John; Grundy, John (Springer Verlag, 2014)
Requirements written in multiple languages can lead to errorproneness, inconsistency and incorrectness. In a Malaysian setting, software engineers are exposed to both Malay and English requirements. This can be a challenging task for them especially when capturing and analyzing requirements. Further, they face difficulties to model requirements using semi-formal or formal models. This paper introduces a new approach, Pair-Oriented Requirements Engineering (PORE) that uses an Essential Use Case (EUC) model to capture and analyze multi-lingual requirements. This approach is intended to assist practitioners in developing correct and consistent requirements as well as developing teamwork skills. Two quasi-experiment studies involving 80 participants in the first study and 38 participants in a subsequent study were conducted to evaluate the effectiveness of this approach with respect to correctness and time spent in capturing multi-lingual requirements. It was found that PORE improves accuracy and hence helps users perform better in developing high quality requirements models.